Long-Term Overgrazing-Induced Memory Decreases Photosynthesis of Clonal Offspring in a Perennial Grassland Plant - Ren, Weibo; Hu, Ningning; Hou, Xiangyang; Zhang, Jize; Guo, Huiqin; Liu, Zhiying; Kong, Lingqi; Wu, Zinian; Wang, Hui; Li, Xiliang (Frontiers in Plant Science, 2017)
Previous studies of transgenerational plasticity have demonstrated that long-term overgrazing experienced by Leymus chinensis, an ecologically dominant, rhizomatous grass species in eastern Eurasian temperate grassland, significantly affects its clonal growth in subsequent generations. However, there is a dearth of information on the reasons underlying this overgrazing-induced memory effect in plant morphological plasticity. We characterized the relationship between a dwarf phenotype and photosynthesis function decline of L. chinensis from the perspective of leaf photosynthesis by using both field measurement and rhizome buds culture cultivated in a greenhouse. Leaf photosynthetic functions (net photosynthetic rate, stomatal conductance, intercellular carbon dioxide concentration, and transpiration rate) were significantly decreased in smaller L. chinensis individuals that were induced to have a dwarf phenotype by being heavily grazed in the field. This decreased photosynthetic function was maintained a generation after greenhouse tests in which grazing was excluded. Both the response of L. chinensis morphological traits and photosynthetic functions in greenhouse were deceased relative to those in the field experiment. Further, there were significant decreases in leaf chlorophyll content and Rubisco enzyme activities of leaves between bud-cultured dwarf and non-dwarf L. chinensis in the greenhouse. Moreover, gene expression patterns showed that the bud-cultured dwarf L. chinensis significantly down-regulated (by 1.86- to 5.33-fold) a series of key genes that regulate photosynthetic efficiency, stomata opening, and chloroplast development compared with the non-dwarf L. chinensis. This is among the first studies revealing a linkage between long-term overgrazing affecting the transgenerational morphological plasticity of clonal plants and physiologically adaptive photosynthesis function. Overall, clonal transgenerational effects in L. chinensis phenotypic traits heavily involve photosynthetic plasticity.